WATCH OUT FOR LANGUAGE FLAWS (WOLF): ENHANCING GRAMMAR LEARNING THROUGH DIGITAL BOARD GAME IN YEAR 4 ESL CLASSROOMS - Nur Ain Nazirah Ash’ari; Nurain Syakirah Abdullah; Melor Md Yunus (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Grammar is essential for effective communication and plays an important role in Malaysia’s curriculum to develop students’ language skills from an early age. However, many students find grammar learning tedious and irrelevant to real-life situations, often struggling to engage with traditional methods like rote memorization. Therefore, this study aims to evaluate the effectiveness of the Watch Out for Language Flaws (WOLF) board game in improving grammar lessons in ESL classrooms and to explore students’ perceptions of the game based on their learning experience. The study involved twelve Year 4 students from primary schools in Dungun, Terengganu, and Johor Bahru, Johor. The development of the WOLF board game using the ADDIE model emphasises a structured approach that ensures the innovation is both engaging and effective in enhancing grammar skills. The research used a quasi-experimental design to assess students’ grammar performance by comparing their results from pre-tests and post-tests. The findings revealed a significant improvement in students’ grammar proficiency after engaging with the WOLF board game. The data also indicated positive feedback, with many participants highlighting its fun and engaging features. The study concludes that integrating innovative tools like the WOLF game into grammar instruction not only improves grammar proficiency but also creates a more engaging and enjoyable learning experience. The innovation is hoped to encourage teachers to move beyond traditional grammar lessons and incorporate more engaging and interactive learning methods. Despite the efficiency, the study recognizes the limitations related to the geographical and demographic factors. Hence, it is recommended for future research to employ broader perspectives from different backgrounds of students to yield greater data. The findings will be able to help to further refine the innovation to accommodate various types of learners.